"I am against Americanizing England. Ordinary TV does not seem to have an elevating influence": class, gender, public anxiety, and the responses to the arrival of commercial television in the Mass Observation Archive, UK. Issue 4 (19th May 2021) - Wood, Helen; Kay, Jilly Boyce
ABSTRACT: This article analyses (broadly lower middle-class) women's responses to the arrival of commercial television in the UK in the 1950s, and seeks to contribute to a more nuanced understanding of British women's relationship to television, consumer capitalism, and modernity in the mid-twentieth century. While women are dominantly figured as especially prone to being seduced by commercial culture at this time, our analysis of material from the Mass Observation archives shows that women in this context were more likely than men to be resistant and hostile to the idea of "sponsored programming". We also show how women's responses reflected and reproduced elitist discourses about "Americanization" as well as the susceptibility of the working classes to the vagaries of commercial culture. We therefore call for a more nuanced and transnational conceptualisation of the historically shifting relationship between women and television.